Penggunaan metode SAW dalam pendukung Keputusan pemilihan pegawai terbaik di MTs Nurul Huda Sukaraja - Miftahul Ulum; Rico Setiawan; Fitri Apriani; Thoha Firdaus (JIKUM: Jurnal Ilmu Komputer, 2025)
The selection of the best employee at MTs Nurul Huda Sukaraja was previously conducted subjectively through teacher voting without a measurable evaluation system. This study aims to implement the Simple Additive Weighting (SAW) method in a decision support system to enhance objectivity and accuracy in assessing employee performance. The method involves assigning weights to criteria such as attendance, discipline, work ethic, and communication, followed by normalization and ranking based on the final scores of each employee. Data were collected through observation, literature review, and interviews. The results showed that the employee named Ariyanto achieved the highest score (2.7061) and was designated as the best employee. The implementation of the SAW method proved effective in facilitating a more fair, systematic, and transparent selection process, supporting human resource management in the school environment.